Uses and Limits of Conventional Corporate Governance Instruments : Analysis and Guidance for Reform - Part Two - World Bank (Washington, DC, 2012)
This private sector opinion is organized in two parts. Part one, published in June 2009, examined the uses and limits of five conventional corporate governance instruments: transparency, independent monitoring, economic alignment, shareholder rights, and financial liability and suggested ways to improve their application. Part two, the essay that follows, recommends how policymakers should approach corporate governance reform generally, with a view toward strengthening the effectiveness of conventional corporate governance instruments. Drawing upon the lessons learned from analyzing the application of conventional corporate governance tools to different situations and contexts, policymakers can take a number of steps to improve corporate governance reform efforts, including: 1) calibrate reforms to fit the surrounding context; 2) assess how an instrument will influence the behavior and focus of the affected parties; 3) be prepared to take difficult decisions to resolve challenging corporate governance issues; 4) ensure coherence of tools employed with the legal, regulatory, and tax regimes; 5) employ 'carrots' as well as 'sticks' to improve corporate governance standards; and 6) focus on social incentives and values to complement existing governance instruments.